Pengaruh Tingkat Partisipasi Angkatan Kerja, Upah Minimum Provinsi, dan Inflasi Terhadap Tingkat Pengangguran Terbuka di Indonesia Tahun 2010-2023 - Permatasari, Defi; Winanto, Asis Riat; Abas, Sayid (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The labor problem that often occurs in Indonesia is unemployment. The high level of unemployment has a direct impact on various aspect of life, especially in the socio-economic dimension. This study aims to analyze the factors that allegedly affect the unemployment rate, namely the labor force participation rate, provincial minimum wage, and inflation. The data used is secondary data obtained from the Central Bureau of Statistics and Bank Indonesia. The analysis technique applied is multiple linier regression analysis using time series data for the period 2010-2023. The result of the analysis shows that simultaneously, the labor force participation rate, provincial minimum wage, and inflation have no significant influence on the open unemployment rate with a significance level (α) of 5%. However, partially only the provincial minimum wage has an effect on the open unemployment rate, while the labor force participation rate and inflation show no significant effect partially on the open unemployment.